Liver venous deprivation for resection of advanced hilar cholangiocarcinoma-a case report and review of the literature - Radoslava Stoyanova; Helmut Kopf; Wolfgang Schima; Wolfgang Karl Matzek; Alexander Klaus (Open Exploration Publishing Inc., 2022)
Hilar cholangiocarcinoma is a rare primary malignancy associated with a dismal prognosis. Currently, complete extended right or left-sided hepatectomy is the primary curative therapy. Achieving a negative resection margin is associated with long-term survival and better quality of life, while post-hepatectomy liver failure (PHLF) due to insufficient liver remnant remains the most dreaded complication with a negative effect on overall survival. Precise preoperative management with sufficient future remnant liver (FRL) volume is the key to achieving good results in the treatment of bile duct carcinoma. To present a case report and a literature review for preoperative FRL optimization prior to major hepatectomies for hilar cholangiocarcinoma. Improvement of postoperative outcomes after extended liver resections in the case of hilar cholangiocarcinoma. A 62-year-old Caucasian woman with Lynch syndrome presented to our department with a hilar cholangiocarcinoma Bismuth type IIIa. The patient had an insufficient future liver volume for extended liver resection. She underwent preoperative preconditioning using a liver venous deprivation (LVD) and underwent two weeks later a right trisectorectomy without any interventional complications. Liver function remained stable postoperatively. The patient was discharged on the 20th postoperative day without major surgical post-operative complications or the need for readmission. LVD is a technically feasible, safe, and effective procedure to increase the FRL in a short period of time with low intra and post-operative complications and therefore improving the survival of patients with hilar cholangiocarcinoma.